CYTOPLASMIC CYLINDRICAL INCLUSIONS INDUCED BY CHICKPEA DISTORTION MOSAIC VIRUS - M. S. PINNER2; F. S. PATIL1, V. R. MALI1, P. G. MARKHAM2, B. WELLS3 (Indian Phytopathology, 2002)
Cytoplasmic cylindrical inclusions (CCI) induced by chickpea distortion mosaic virus (CCI) in cells of Cicer arietinum L.cv. Chaffa were studied by electron microscopy. CCI appeared as pinwheels and scrolls in cross-sections and bundles and tubes in longitudinal sections. Neither laminated aggregates nor dense bodies were observed in thin sections of chickpea tissue. infected by CpDMV. No CCI were observed in healthy chickpea cells. CCI morphology induced by CpDMV -resernbles subdivision I type inclusions of the potyvirus group. The CCI induced by CpDMV are distinctive and can be used to separate infections of chickpea caused by CpDMV from those caused by other potyviruses.